2016
DOI: 10.4102/phcfm.v8i2.1016
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of application of the Basic Antenatal Care principles of good care and guidelines in pregnant women’s antenatal care records

Abstract: BackgroundBasic Antenatal Care (BANC) is an approach that is used in the public health institutions of South Africa to provide health care services to pregnant women. The approach was introduced as a quality improvement strategy based on the belief that good quality Antenatal Care (ANC) could reduce maternal and perinatal mortalities and improve maternal health.AimThe aim of this study was to analyse pregnant women’s ANC records for evidence suggesting that the BANC principles of good care and guidelines were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…For the antenatal cases, the overall completeness was about 82%-88% with lower quality for treatment (27%-78%) and laboratory findings (35%-43%) [39]. Another study from South African observed missing information for 54%-98% of antenatal cases [40]. We also documented lower (case record completeness and quality at baseline, which improved to 90% for most of the components with the QI efforts across the facilities and districts.…”
Section: Plos Onementioning
confidence: 56%
“…For the antenatal cases, the overall completeness was about 82%-88% with lower quality for treatment (27%-78%) and laboratory findings (35%-43%) [39]. Another study from South African observed missing information for 54%-98% of antenatal cases [40]. We also documented lower (case record completeness and quality at baseline, which improved to 90% for most of the components with the QI efforts across the facilities and districts.…”
Section: Plos Onementioning
confidence: 56%
“…Similar findings have been reported from other research in South Africa, for example in the context of antenatal care guideline adherence. 56 This is a global challenge, with the WHO recognising the importance of quality health workforce training in realising UHC. 57 One of the contradictions from our findings was that despite training gaps and primary care provider workload, one of the doctors said that 'nurses know more than doctors'.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence comes as a concern, while there is a universal rule in nursing that "what is not recorded is regarded as not being done". 26 This emphasizes good record-keeping across nursing and midwifery practices, as it is considered integral to the quality and effective care. Congruently, the South African guidelines for maternal care prescribe standards for medical record-keeping during antenatal care.…”
Section: Discussionmentioning
confidence: 99%